The Role of Environmental-Based “Green Startup” in Reducing Waste Problem and its Implication to Environmental Resilience - Oki Sadma (Research Horizon, 2021)
The waste problem has become a global public concern in sustainable development goals (SDGs) through the concept of "zero waste". The uncontrolled waste problem causes environmental quality degradation which then affects the environmental resilience of an area. The application of green business practices in a green startup companies is one of the business development models that supports the goals of a green economy and environmental sustainability. This study aims to find the development of a green startup of “Sampah Muda” in reducing waste problem in Semarang City and to describe the implication of developing a green startup “Sampah Muda” to environmental resilience. The results demonstrate that the development of “Sampah Muda” is carried out by implementing environmental-based business practices through the application of green startup characteristics and based on the right development basis as a determining factor for the startup success factors. Research shows that the development of environmental-based startup "green startup" “Sampah Muda” has positive implications for environmental resilience. Environmental resilience conditions are reflected in the preservation of environmental elements including abiotic, biotic, and socio-cultural from the implementation of environmental ethics in startup activities.